Effect of preload and shim types on the mechanical properties of composite-aluminium bolted joints. (January 2022) - Yue, Xuande; An, Luling; Chen, Zengtao; Cai, Yuebo; Wang, Chufan
The influence of both preload and the presence of shim types on the mechanical properties of composite-aluminium single-bolt, single-lap joints were studied in this paper. The load-displacement curve and surface strain field of joints in different shim types and preloads were obtained through tensile experiments. A progressive damage model was established using the UMAT subroutine in ABAQUS. A hybrid failure criterion and a linear continuous degradation model were used to describe the progressive damage of composite laminates. The results show that for joints with no shim and for those with various types of shims, the tensile stiffness, peak load and initial damage load could be reduced when the preload is insufficient or too large. Compared with joints with no shims or with peelable fibreglass shims, joints with liquid shims required a larger preload to achieve the best mechanical properties. As the proportion of peelable fibreglass shim increased, the tensile stiffness and peak load continued to increase in joints with a mixed shim of liquid and peelable fiberglass shim. Shims can serve as tension bearings, but have little effect on the initiation and development of bearing failure.